STRATEGI PEMBELAJARAN PENDIDIKAN MULTIKULTURAL BERBASIS BUDAYA LOKAL - Murdiono, Mukhamad (PKn Progresif, 2012)
Nation Indonesia is a multicultural nation, therefore, education should be developed in accordance with the conditions of a multicultural society. Appropriate education for development in a multicultural society is multicultural education. In a study of multicultural education is necessary to increase the awareness that all learners have special characteristics because of their age, religion, gender, social class, ethnic, racial, or cultural characteristic embedded in each self. Multicultural education deals with the idea that all learners regardless of their cultural characteristics, should have equal opportunities to learn in school. Differences that exist between them is a must, and that difference must be received in reasonable not to discriminate. In order to achieve the goals of multicultural education needs to develop appropriate learning strategies and appropriate, one of which is based on learning the local culture. Local culture is a culture that is direct, close, and physically is all around us. Local culture is usually introduced by family and close relatives. Each region in Indonesia has a specificity that can be the regional identity. The specificity could be because of race, history, location, religion, and beliefs espoused. Diversity and distinctiveness can be used by teachers in developing multicultural education.